2013
DOI: 10.1371/journal.pone.0083005
|View full text |Cite
|
Sign up to set email alerts
|

The Disease-Specific Phenotype in Cardiomyocytes Derived from Induced Pluripotent Stem Cells of Two Long QT Syndrome Type 3 Patients

Abstract: Long QT syndromes (LQTS) are heritable diseases characterized by prolongation of the QT interval on an electrocardiogram, which often leads to syncope and sudden cardiac death. Here we report the generation of induced pluripotent stems (iPS) cells from two patients with LQTS type 3 carrying a different point mutation in a sodium channel Nav1.5 (p.V240M and p.R535Q) and functional characterization of cardiomyocytes (CM) derived from them. The iPS cells exhibited all characteristic properties of pluripotent stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 36 publications
2
51
0
Order By: Relevance
“…The group also found prolonged AP duration in SCN5A mutant cells. Similar observations were made using iPSC-CMs from LQTS-3 patients, however with different mutations in the SCN5A gene [78]. Using patch clamp to study Na + and Ca 2+ currents, as well as whole-cell current clamp to measure AP, they found that LQTS cells have tendencies toward prolonged AP duration, smaller Na+ current density, slower time to inactivation, and increased time to peak.…”
Section: Disease Modelssupporting
confidence: 62%
“…The group also found prolonged AP duration in SCN5A mutant cells. Similar observations were made using iPSC-CMs from LQTS-3 patients, however with different mutations in the SCN5A gene [78]. Using patch clamp to study Na + and Ca 2+ currents, as well as whole-cell current clamp to measure AP, they found that LQTS cells have tendencies toward prolonged AP duration, smaller Na+ current density, slower time to inactivation, and increased time to peak.…”
Section: Disease Modelssupporting
confidence: 62%
“…4A), AP parameters (Vm ,10 V/s and AP duration at 90% [APD 90 ] of # 150) [36,37] and mean beating rate .100 (supplemental online Fig. 4B, 4C).…”
Section: Electrophysiological Properties Of Human Cms Differentiated mentioning
confidence: 99%
“…66 Fatima et al likewise had difficulty showing increased ADP in LQT3 hiPSC-CMs derived from patients carrying different SCN5A mutations (p.V240M and p.R535Q) because of variations in the EP parameters among individual hiPSC-CMs. 68 These findings underscored the current limitations of hiPSC models, including the inability to accurately recapitulate all clinical disease thus far.…”
Section: Disease Modeling Using Patient-specific Hipsc Derivativesmentioning
confidence: 80%